Out of Office? Analysis of Computer-Mediated Communication Tools within Organisational Communication Strategies: Remote Working Style - Özkan, Beste Naz (Filológia.hu, 2024)
Most of the organisations have started to challenge the remote working process after the pandemic. It is very important to keep the employees motivated and satisfied during remote work. In this sense, the organisational communication structure of a company plays a major role. But it is still questionable how computer-mediated communication affects employees’ motivation as a tool of organisational communication. The aim of this research is to examine computer-mediated communication as a tool of organisational communication on motivation and satisfaction of employees in remote working processes. The applied methodology of this research is in-depth interviews with remote workers for more than one year. According to the results, it can be stated that the motivation of remote working employees is usually dependent on the correct organisational communication structure. Since they always use computer-mediated communication to communicate with team members and managers, it is essential to have a correct organisational communication flow to build a healthy working atmosphere. As a conclusion, the present study mentions that organisations need to constitute the environment of satisfaction and motivation towards other team members and must try to create a trustable and comfortable communication flow through emerging communication technologies.